Barriers to Managing Childhood Obesity in the General Practice Amidst of the Double Burden of Malnutrition: A Sri Lankan Perspective - M. G. D. V. K Kiridana (International Journal of General Practice, 2024)
Childhood obesity is on the rise, mostly in the low-income regions in South Asia including Sri Lanka. Simultaneously, undernutrition also continues to be an ongoing public health issue. The coexistence of childhood obesity with undernutrition has resulted in a double burden of malnutrition in these countries. Management of obesity in a community already affected by undernutrition is a challenging situation. At present, management of childhood obesity occurs as a hospital-based lifestyle modification intervention which cannot address all tiers in the community alike. Although national level multifaceted strategies are in place, implementation is limited due to financial constraints. In this context, the general practitioners can be considered as an important group of medical professionals who can reach families in the community. In many households in Sri Lanka, an overweight child is considered as normal and well-nourished in comparison to an underweight child. Unhealthy eating habits and force feeding have become norms in the society. Changing mindsets of people need significant time and commitment. General practitioners, in the community would be able to achieve this target through effective communication based on a nutrition sensitive approach. While uplifting the infrastructure facilities, steps have to be taken to update the knowledge and communication skills of the general practitioners on managing childhood obesity in a community affected with double burden of malnutrition. The well-equipped GP is an asset to modify the attitudes and thinking patterns of parents with regard to child nutritional problems. Childhood obesity is on the rise, mostly in the low-income regions in South Asia including Sri Lanka. Simultaneously, undernutrition also continues to be an ongoing public health issue. The coexistence of childhood obesity with undernutrition has resulted in a double burden of malnutrition in these countries. Management of obesity in a community already affected by undernutrition is a challenging situation. At present, management of childhood obesity occurs as a hospital-based lifestyle modification intervention which cannot address all tiers in the community alike. Although national level multifaceted strategies are in place, implementation is limited due to financial constraints. In this context, the general practitioners can be considered as an important group of medical professionals who can reach families in the community. In many households in Sri Lanka, an overweight child is considered as normal and well-nourished in comparison to an underweight child. Unhealthy eating habits and force feeding have become norms in the society. Changing mindsets of people need significant time and commitment. General practitioners, in the community would be able to achieve this target through effective communication based on a nutrition sensitive approach. While uplifting the infrastructure facilities, steps have to be taken to update the knowledge and communication skills of the general practitioners on managing childhood obesity in a community affected with double burden of malnutrition. The well-equipped GP is an asset to modify the attitudes and thinking patterns of parents with regard to child nutritional problems.
Keywords: double-burden of malnutrtion